Teaching healthy eating habits to children, to maintain good health throughout life through Greek primary school textbooks 1975-2020. [Enseigner de saines habitudes alimentaires aux enfants, afin de préserver une bonne santé toute la vie à travers les manuels scolaires de l’école primaire grecque1975-2020] - Archontia VASILOPOULOU (Nutrition & Santé)
Introduction. The construction of nutritional consciousness is a continuous procedure, which starts from childhood. It has been found that eating habits are configured early in life. Objectives. To research the number of references and to evaluate their quality concerning the dietary habits theme in primary school textbooks, published since 1975. Additionally, the diachronic nature of this study allowed for comparison among the references encountered in the three different chronological periods. Material and methods. The books of primary school, including physical sciences subjects, constituted the body of the study, edited from 1975-2020, since they are the main source of nutritional information for students. Results. The methodology of study was defined as thematically analysis of the books content and was based on the categorization of words and phrases, according to their content. All the relevant refe-rences were searched and placed together in a table. The study of school books revealed four themes concerning the recommended food habits, such as the avoidance of overeating, the consumption of all the food groups, and daily meals and the preference of fresh fruit and vegetables. Conclusion. The content of the present books requires additions and improvements, in order to be in accordance with the updated scientist data and the contemporary mode of alimentation. [Introduction. L’enseignement des habitudes alimentaires saines est une procédure continue et complexe, qui est initiée depuis l’enfance. Objectifs. Rechercher le nombre de références et évaluer leur qualité concernant le thème des habitudes alimentaires dans les livres scolaires de primaire, édités depuis 1975. De plus, le caractère diachronique de cette étude permet la comparaison parmi les références retrouvées sur les trois différentes périodes chronologiques. Matériel et méthodes. Le corpus de la présente étude inclut les manuels scolaires grecs de primaire, qui ont été édités depuis 1975 jusqu’à 2020. Les livres choisis traitent des thèmes des sciences physiques.La méthodologie effectuée concerne l’analyse thématique de contenu des livres, qui est fondée sur le regroupement des mots et phrases selon leur contenu. Ainsi, toutes les références pertinentes dans les livres ont été relevées et regroupées au sein d’un tableau. Résultats. L’étude thématique des manuels examinés a relevé quatre sous-thèmes sur le thème des habitudes alimentaires saines. Ces sous-thèmes concer-nent des recommandations sur l’évitement de la surconsommation alimentaire, la consommation de tous les groupes d’aliments, la consommation de plusieurs repas par jour et la consommation des fruits et végétaux frais. Conclusion. Le contenu des manuels scolaires contemporains requiert des améliorations et des additions, confor-mément aux données scientifiques actualisées ainsi qu’au mode d’alimentation contemporain.]